The Latest Research Progress of m6A Modification and Its Writers, Erasers, Readers in Infertility: A Review - Liu, Xuda; Wang, Haiying; Liu, Bingchen; Qi, Zhipeng; Li, Jiashuo; Xu, Bin; Liu, Wei; Xu, Zhaofa; Deng, Yu (Frontiers in Cell and Developmental Biology, 2021)
We summarized the scientific literature published from 2012 to 2020 on the effects of RNA methylation m6A modification on the fertility of both sexes. We focused on the effects of m6A modification (e.g., methyltransferase 'Writers', demethylase 'Erasers', binding protein 'Readers') on gametogenesis (e.g., spermatogenesis, oogenesis). Literature review shows that RNA methylation m6A modification may be related to infertility. Potential explanations for this association can be generated from experimental studies. Specifically, m6A modification catalyzes the formation of m6A of mRNA under the influence of methyltransferase, completes the demethylation of mRNA by demethylase, and then is specifically recognized by m6A binding protein, which plays an important role in the process of gametogenesis. Normal gametogenesis is the basic guarantee for fertility, and the dysfunction of m6A modification is likely to cause obstacles to gametogenesis, leading to infertility. This has promoted in-depth research on the RNA methylation mechanism of gametogenesis, in order to better understand the close relationship between m6A modification and gametogenesis and fertility, and provide potential preventable targets for the treatment of infertility. And provide clues for the research and development of related drugs, so such research has important positive significance.